Cartwheel aerenchyma in Cardamine amara as a model of schizogenous tissue formation in plants - Hiroshi Kudoh; Masato Sakane; Karol Marhold; Rie Shimizu-Inatsugi; Kentaro K. Shimizu; Hidehiro Fukaki (iScience, 2025)
Summary: Root aerenchyma is essential for survival under waterlogged conditions for plants. It has been necessary to explore a model system of schizogenous aerenchyma in Brassicaceae. Here, we report the formation of schizogenous aerenchyma in primary roots of seedlings of Cardamine amara showing a rather simple cartwheel pattern. The formation of the aerenchyma was suggested to involve three developmental processes: (1) formation of a three-layered cortex, (2) circumferential division of the outer layer of the cortex, and (3) circumferential detachment of cells in the middle layer of the cortex. The root aerenchyma of the C. amara seedling discovered here is the simplest one ever reported, and is a suitable candidate for the model of schizogenous aerenchyma development in plants.